Impact of policies on raw material procurement in the Vietnamese timber processing industry: a case study of sawmills in Hue City. Issue 2 (3rd March 2020) - Iwanaga, Seiji; Duong, Dang Thai; Minh, Nguyen Van
ABSTRACT: In Vietnam, the expansion of plantation forests, the logging ban in natural forest, and the partial timber import ban were predicted to drastically change the industry's procurement of raw material. We investigated the response of timber processing companies to these events and policies, and discuss the future development of Vietnamese sawn timber industry. First, we considered the macroeconomic trends: timber imports from far-off countries have increased, and the expansion of plantation forests has also increased timber consumption. Second, interviews on sawmills in Hue City show that the events and policies have impacted the sawmills' choice of raw material such shifting from Laotian timber to southern Africa timber due to the partial import ban of timber, from natural forest timber to southern Africa timber due to the logging ban in natural forest, or from natural forest timber to plantation forest timber due to both the logging ban in natural forest and plantation forest resources expansion. Regarding the impact of policies on the change of operation scale, the strategy of procurement for raw material in each sawmill is a significant element. Especially in the case of plantation forest timber, even though sawmills may consume the same plantation forest timber, business strategies, such as aggressive procurement of timber and obtaining timber source certification, have effects on the rate of development among sawmills.